Narasi Tunawisma Dalam Film Dream: Struktur Narasi A.J. Greimas - Amelia, Fajrina; Gita Sukmono, Filosa (Universitas Muhammadiyah Magelang, 2025)
This study aims to determine how actantial and functional structures form narratives about homelessness and how the process of social transformation of homelessness is analyzed through binary opposition and the semiotic square as supporting tools in A.J. Greimas' narrative framework. This study uses a qualitative descriptive method with a document study approach. Data was collected through non-participant observation of the film, systematic recording of scenes and dialogues, and the development of narrative structures. Data were analyzed using the Miles & Huberman model, which includes data reduction, data presentation, and drawing and verifying conclusions. The results of the study show that the homeless character in the film Dream is not only a complement to the story but also a driver of the storyline that undergoes a narrative transformation from a passive object to an active subject. This transformation occurs gradually through several shifts in value from passive to active, unworthy to worthy, and powerless to empowered. Thus, this study shows that the film Dream depicts the homeless as a group that can have an important role, not just a marginalized group. This film is also a social critique of marginalized groups' lack of recognition and position in society